Aplikasi Identifikasi Wajah Berbasis Android - Widiakumara, I Kadek Surya; Putra, I Ketut Gede Darma; Wibawa, Kadek Suar (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 3 Desember 2017DO - 10.24843/LKJITI.2017.v08.i03.p06, 2017)
Identification technology has been widely developed today, such as fingerprint identification, palms and face. Identification is the determination of a person's identity and the process of identifying is an activity in determining or establishing a person's identity. Development of this identification technology has been applied to various devices one of them on Android based smartphone. Most of the development of Android based identification is still use storage technology on the device itself. The Eigenface method is used to extract the relevant information from a face image, then convert it into the most efficient set of codes and the code is compared to the code from the properties it has stored in the database. Face Identification Application Android Based is built by using storage technology on the server (MySQL) and also use the Eigenface Method. The success rate of face identification test results was 68% and the false accept rate of 32% , of the total trial was 25 times identification. Some important factors that influence the success rate of identification are the position of the face and the intensity of light during enrollment .